Cosmopolitanism of the Sultanate of Banten: An Overview of Settlement and Social Structure of the 15th Century - Tubagus Umar Syarif Hadi Wibowo (IHiS (Indonesian Historical Studies), 2021)
This study aims to examine the cosmopolitanism of settlements and social structures in the Sultanate Banten in the 15th century which became one of the centers of the pepper trade in Southeast Asia. Using the historical method, this study reveals the findings that geographical and economic factors that trade through maritime have brought the Sultanate of Banten to become a cosmopolitan city with various cultures from and outside the archipelago that interact with each other. In this study, identification on economic background, occupation, status, and religion of the community in the Sultanate Banten. In addition, the structure or social layer became the basic policy of the sultan to implement the distribution of settlements for the people living in the center of the Sultanate of Banten.